ENGLISH-ROLE OF ISLAMIC LEADERSHIP: EFFECT OF HEAD TEACHER TRANSACTIONAL LEADERSHIP STYLE ON TEACHERS’ PERFORMANCE AT ELEMENTARY LEVEL - Muhammad Javid; Muhammad Tahir Khan Farooqi; Rashid Latif (دی اسکالر)
Transactional leadership style is the general way through which a leader behaves toward his subordinates to attain objectives. It plays a very important role in the success of an organization. The main objective of this attempt was to examine the effects of the head teachers’ transactional leadership style on teachers’ performance at the elementary level schools. The study was quantitative and descriptive. The target population of this study was comprised of all male and female elementary school teachers in the province of Punjab, while the accessible population of the study was comprised of all male and female elementary school teachers in Sahiwal Division. A sample of 343 teachers was selected through the convenience sampling technique (192 males and 151 females). The cross-sectional survey was used to collect data through the multifactor leadership questionnaire (MLQ) and the teachers’ performance evaluation scale (TPES) from elementary school teachers. The collected data were tabulated and analyzed through SPSS software for both descriptive and inferential statistical approaches. The researcher applied t-test and ANOVA for comparison, Pearson for relationship, and regression for measuring the effects of head teacher transactional leadership style on teachers’ performance at the elementary level. The main findings of the study revealed that there was a significant effect of the head teacher’s transactional leadership style on teachers’ performance at the elementary school. Moreover, contingent reward and management by exception (active) were positively correlated with all teachers’ performance subscales, and management by exception (passive) was negatively correlated with all teachers’ performance subscales.